La contextualización del currículo, un medio para potenciar el desarrollo - Flor María Azofeifa-Castro (Revista Electrónica Educare)
The author describes the experience of taking into account the curriculum for the microcultural dimension (school) and the macrocultural dimension (community) in primary schools in Guápiles, Limón and Pérez Zeledón.